Exploring the effects of intrinsic aging on human skin: a histologic perspective - Sahib, Ahmad Hassan (American Journal of Biodiversity, 2025)
Aging remains an inevitable and irreversible phenomenon affecting all living beings. In humans, skin aging carries unique importance due to the critical role appearance holds in contemporary common dynamic. Understanding the structural transformations that occur with aging is essential for comprehending its underlying mechanisms, which is a critical step toward managing, addressing, and potentially reversing these changes. This research underscores the significance of skin aging in healthcare and society by examining the microscopic, morphological, histological, and architectural changes associated with intrinsic aging. Through a histological study of a protected body area, it isolates internal aging effects, focusing on alterations in epidermal thickness and basement membrane structure. During numerous surgical interventions at Al-Hussein Teaching Hospital in Dhi Qar Governorate, skin samples were composed from the anterior abdominal region of 24 male participants spanning different age ranges. Consent for participation was obtained beforehand from all research specimens. The participants were categorized into four separate age categories: group one (ages 0–11), group two (ages 12–24), group three (ages 25–50; n = 6), and group four (ages 51 and above), with 6 participants included in each group. All contributors had to be selected carefully to ensure they did not have previous experiences of hypertensive or hyperglycemia. In the younger age group, the epidermis displayed a consistent and organized cell arrangement across all its layers. In contrast, the older age group exhibited a noticeable reduction in epidermal thickness. A statistically significant difference was identified between the younger and adult groups (Groups 1 and 2) compared to the older age group (Group 3). Furthermore, the thickness of the epithelial basement membrane exhibited a marked increase with advancing age. The examination exposed a decline in epidermal thickness and a reduction in the degree of interdigitation between layers as age progressed. Meanwhile, the papillary dermis verified a considerable increase in thickness, unlike the reticular dermis, which remained relatively unchanged. Specifically, the papillary layer underwent significant expansion, whereas the reticular dermis exhibited a reduction in thickness. Aging was also associated with a decrease in cellular density and vascularization within both dermal layers. This morphometric evaluation of photo-protected skin highlights the substantial impact of endogenous aging concerning with structural integrity of cutaneous layer. Aging significantly impacts the cutaneous composition, basement membrane architecture, besides overall cellular composition.